Current trends and legal issues in special education - Bateman, David, 1963-; Yell, Mitchell L. (Thousand Oaks : Corwin A SAGE Company, 2019)
Many special education leaders have worked for years in special education as either teachers or related services providers, and most states have standards for certification for the role of the special education administrator/leader. With their broad formal education and years of experience, they should be able to meet the challenges of building and program leadership. Special education leaders need to be prepared to tackle any problem related to teaching and learning, personnel selection and evaluation, basic financial management, parent and community relations, and legal matters related to special education. However, just like other school leaders, many in special education are overwhelmed with the demands of the job while at the same time having to provide services with an increasing diverse population in an underfunded system and growing negative public perception of the education system. Special education leaders will experience the burden of many responsibilities in their position, such as fulfilling the spirit and letter of the law regarding students with disabilities, helping staff keep abreast of best practices and meeting the ever-increasing demands from communities and families. They can suddenly be thrust into situations in which they must become the final arbiter on matters related to plethora of processes and procedures such as IEP team meetings, manifestation determinations, requests for mediation or due process hearings, and IDEA compliance. It is likely that many of these will be new leaders who will need guidance and direction as they move the teams ahead. Special education leaders are expected to be experts on all levels and types of special education services available within and outside of the district, every disability, and all aspects of special education programming from early intervention to post-secondary transition. Recognizing that few administrators feel adequately prepared for these roles, Special Education Leadership will be developed to enable practicing leaders to build and support effective special education programs to include supervising and supporting teachers, review programs, and implement special education law.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Special education -- Law and legislation; Special education teachers